Integrasi Teknologi Pengolahan Ikan dalam Pendidikan Pertahanan untuk Mendukung Ketahanan Pangan Nasional - Dwi Scativana Isnaeni (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2025)
Indonesia possesses vast potential in fisheries; however, traditional fish processing still faces limitations such as short shelf life, quality variability, and food safety risks. This study aims to review innovations in traditional fish processing, analyze the comparison between traditional and modern products, and formulate a framework for integrating technology-based products into defense education to support national food security. The method used is a Systematic Literature Review (SLR) of 72 scientific publications from 2015 to 2025, analyzed through quantitative, thematic, and meta-interpretive synthesis approaches. The results show that modern technologies—such as vacuum drying, quick freezing (IQF), canning, surimi, and smart packaging—can extend the shelf life of products 2–5 times longer than traditional methods, while maintaining nutritional quality and microbiological stability. These technologies preserve protein retention at 95–100%, minimize omega-3 degradation, and reduce the risk of microbial and chemical contamination. Integrating technology-based products into defense education modules through experiential learning enables participants to acquire technical, strategic, and cultural competencies, as well as an understanding of military food logistics, food safety risk mitigation, and food distribution management in emergency situations. This transformation also supports the preservation of local culture, the application of blue economy principles, and national food sovereignty in a sustainable manner. This research contributes both academically and practically by connecting food technology, defense education, and the preservation of traditional culinary practices, providing a framework for developing learning modules and cross-stakeholder collaboration. The findings can serve as a reference for policymakers, educators, and industry practitioners to improve the nutritional quality, safety, and sustainability of processed fish products, while building adaptive and resilient defense human resources.